Pertumbuhan Bibit Buah Naga (Hylocereus polyrhizus) pada Berbagai Panjang Stek dan Komposisi Media Tanam - M. Iqbal; Nur Hafizah; Zarmiyeni Zarmiyeni (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2018)
Dragon fruit is one of the cactus plants which is quite popular because of its sweet taste and unique and interesting shape. Propagation of dragon fruit seeds is usually done by cuttings and one of the problems in the supply of dragon fruit seeds is the planting medium. This study aims to determine (i) the effect of the interaction of various cuttings lengths and composition of the planting medium, (ii) the effect of various lengths of cuttings, (iii) the influence of various plant media compositions, (iv) the best interactions between various cuttings and composition of planting media, (v ) the best length of cuttings and (vi) the best media composition in dragon fruit cultivation. This study was conducted in Haur Gading Village, Batang Alai Utara District, Hulu Sungai Tengah Regency from May-August 2018, using Factorial Randomized Block Design (RBD) 2 factors. The first factor is the length of cuttings with 4 levels: p1 = 35 cm, p2 = 40 cm, p3 = 45 cm, p4 = 50 cm. The second factor is the composition of the planting medium with 3 levels: k1 = 1.5 kg of soil: 0.0 kg wallet dirt fertilizer: 1.5 kg of sand, k2 = 1.0 kg of soil: 1.0 kg of wallet dirt fertilizer: 1, 0 kg of sand, k3 = 0.5 kg of soil: 1.5 kg wallet dirt fertilizer: 1.5 kg of sand. The results showed that the interaction of the length of cuttings with the composition of the planting medium had no effect on growth, while the single length factor of the cuttings had no effect on all observation variables except the shoot length had a significant effect on week 12 WAP and the composition of planting media influenced the growth of dragon fruit seeds.